Generational diversity, personal attributes and organizational commitment: a study among employees of corporate consultancies - Purani, Verasamy (2018)
The main objective of this study is to identify the relationship of generational diversity, work values, attitudes & behavior and interpersonal skills towards organizational commitment among employees from corporate consultancies in Kuala Lumpur. The research framework contained four independent variables, namely generational cohort, work values, attitude & behavior and interpersonal skill. The dependent variable of this study is organisational commitment (affective, continuance and normative). The targeted population for this study is employees from fifteen (15) corporate consultancies in Kuala Lumpur. This research used survey method. 436 questionnaires were distributed and 241 questionnaires were received back. The response rate is 55.27%. Statistical Package software for Social Science (SPSS) Version 21.0 was used to analyse the data. One- Way ANOVA and Pearson correlation coefficient were used to test the hypothesis. One- Way ANOVA shows that there is significant difference among three generational cohort of employees on organizational commitment (affective, continuance and normative). The Pearson correlation coefficient shows there is significant relationship between work values, attitude & behavior and interpersonal skill of three generational cohorts towards organizational commitment (affective, continuance and normative)